2021
DOI: 10.1097/inf.0000000000003116
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to the Surveillance of Pediatric Infectious Diseases From Ambulatory Pediatricians in the Digital Era

Abstract: Background: Many ambulatory networks in several countries have established syndromic surveillance systems to detect outbreaks of different illnesses. Here, we describe a new Pediatric and Ambulatory Research in Infectious diseases network that combined automated data extraction from the computers of primary care pediatricians. Methods: Pediatricians who used the same software, AxiSanté 5-Infansoft for electronic medical records were specially trained in infectious diseases, encouraged to comply with French tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Virological surveillance from week 24 showed that this epidemic was mainly associated with the CVA6 type. The biannual pattern in summer and autumn was similar to that usually expected for these diseases in Europe or Asia [2,4,7]. However, the 2021 epidemic was characterised by a sharp rise in the summer and an earlier autumn peak compared with previous years.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Virological surveillance from week 24 showed that this epidemic was mainly associated with the CVA6 type. The biannual pattern in summer and autumn was similar to that usually expected for these diseases in Europe or Asia [2,4,7]. However, the 2021 epidemic was characterised by a sharp rise in the summer and an earlier autumn peak compared with previous years.…”
Section: Discussionsupporting
confidence: 71%
“…Since September 2017, PARI has been conducting prospective surveillance of the most common paediatric infectious diseases seen in outpatient settings. The EV-associated mucocutaneous illnesses HFMD/HA are included in the PARI surveillance panel [4]. The PARI network includes 113 paediatricians (as at September 2021; ca 4% of all French paediatricians) located throughout all French metropolitan regions except Corsica and is coordinated by the Association Clinique et Thérapeutique du Val de Marne (ACTIV).…”
Section: Syndromic Surveillance For Hand Foot and Mouth Disease And Herpanginamentioning
confidence: 99%
See 1 more Smart Citation
“…In 2017, we set up a nationwide pediatric ambulatory infectious disease surveillance network (PARI, Pediatric and Ambulatory Research in Infectious diseases) to assess trends of in pediatric infectious diseases before and after the implementation of nationwide health interventions. 19 This study allowed us to observe the impact of the COVID-19 pandemic on infectious disease frequency, which sharply decreased in 2020. 19 While the pandemic remained ongoing for 2 years, the burden of COVID-19 is now reduced, and NPIs have been gradually lifted, the aim of this study is to investigate the trends of pediatric ambulatory infectious diseases before and up to two years after the onset of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…A significant decline in infection rates was reported for pneumococcal diseases 18 , 19 , N. meningitidis infections 19,20 , pertussis 21 , 22 , varicella 21 , 23 , measles 21 , enterovirus infections 23 , influenza 5 , 23 , 24 , 25 and RSV infections 5 , 24 , 26 , 27 , 28 .…”
Section: Unusual Surge Of Respiratory Syncytial Virus Infections In Children Amid the Ongoing Pandemicmentioning
confidence: 99%